Profile of Chronic Mental Disorder Patients with or without Suicide Ideation in the Psychiatric Ward of Dr. Soetomo General Hospital, Surabaya - Khoirun Nada Salsabila; Khairina Khairina; Lilik Djuari (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Risk factors for suicide ideation or suicide are the history of mental illness, family history with suicide or depression, and having suicide attempts. This study aimed to determine patients with mental disorder profiles that had suicide ideation and never had suicide ideation. This study also aimed to identify the intensity of suicide idea and history of suicide attempts at a subject that had suicide ideation.Methods: This was a descriptive observational study. This study was conducted using C-SSRS questionnaires and some additional interviews with chronic mental disorder patients in the Psychiatric Ward, Dr. Soetomo General Hospital, Surabaya.Results: Total patients that had suicide ideation were 11 patients, consisted of 8 patients with schizophrenia, and 2 patients with bipolar disorder. The mean length of illness was 16.55 years, GAF Scale when suicide ideation appeared was at range 40-31 until 60-51. GAF Scale got better in range 60-51 until 80-71, mostly in teenagers and adults when suicide ideation appeared, primarily women. Many of them were unemployed, had lower income, did not have income, and were non-college graduates. The total subjects that never had suicidal ideation were 23 patients, 2 of them with depression, mean age of illness onset was 12.04 years old, the balance between women and men, some of them were sellers and worked in a private field, with income range between 2 until 5-6 million, and few of them were college graduates.Conclusion: Suicide ideation was mostly found in some subjects with younger age, had longer length of illness, had lower GAF Scale, primarily women, unemployed, had lower income, and had lower education.